Enhancing ecosystem dynamics: organic and regenerative practices in rice–wheat systems and their impact on soil arthropod biodiversity - Mishra, Ajay Kumar; Tiwari, Ankita; Maurya, Piyush Kumar; Sharma, Sheetal (Frontiers in Environmental Science, 2024)
Arthropods may make a significant fraction of the total number of soil organisms. They function as plant litter transformers or ecosystem engineers and thus contribute positively to soil health. The present study was conducted during the 2020-2022 at International Rice Research Institute, South Asia Regional Centre, Varanasi. Study investigates the impact of different farming methods-conventional (Scenario 1; Sc1), LINF-Low-input natural farming (Sc 2); BBEF-Biochar-based ecological farming (Sc 3); CROF-Climate-resilient organic farming (Sc 4); RF-Regenerative farming (Sc 5) practices on soil arthropod populations in rice-wheat systems.Study utilized pitfall traps across various experimental setups. The findings revealed a significant increase in arthropod diversity and abundance, particularly in organic farming scenarios, where the Formicidae family (ants) and the Araneae family (spiders) were most prevalent. In an organically rich soil system, the five most diverse groups (Isopoda, Myriapoda, Insecta, Acari, and Collembola) were reported. This increase can be attributed to the nutrientrich amendments that positively influence soil organisms. This study highlights a gradual increase in specific taxa, such as cockroaches, spiders, ants, and grasshoppers, following the transition to organic farming. Principal component analysis (PCA) further revealed distinct arthropod distribution patterns in the different farming systems, indicating the unique ecological impact of each method. Interestingly, predator populations in zero-till wheat fields under regenerative agriculture were greater than those in conventionally tilled fields. These results underscore the substantial role of organic and regenerative farming practices in promoting sustainable agricultural ecosystems. This study reveals the complex interplay between farming practices and arthropod dynamics and highlights the ecological benefits of sustainable agricultural methods, emphasizing their potential to enhance biodiversity and ecosystem health.